Framing genetically modified (GM) food: a content analysis of GM food coverage in the New York Times, Le Monde and the Straits Times (1992-2001). - Chan, Royston Chow Yang. (2008)
This study seeks to find out how genetically modified (GM) food news is framed in three national dailies from the United States, France and Singapore, who aim to become biotechnology leaders in their respective regions.